Абдирахмановтың сатиралық гүрриңлеринде көркем шеберлик - Сейтбеков, А.Б. О (SCIENCE and SOCIETY, 2025)
The article focuses on the study of the mastery of creating images in the satirical works of O.Abdurakhmanov.
Keywords: writer; image. drama writer; janre; play; tragedy; stor; epic novel